PEMBELIAN IMPULSIF PADA E-COMMERCE SHOPEE (Studi pada Konsumen Shopee di Jakarta Selatan) - Simon Tumanggor (2021)
Competition in the e-commerce world is growing and fierce. Every time e-commerce give offers and offers to interst consumer. So, consumer choose a place to shop especially Shopee Indonesia. The purpose of this study is to know and analysis the effect of sales promotion, product quality and electronic word of mouth on impulsif buying. The object is e-commerce Shopee. This research using purposive sampling technique and choose 75 respondents based on criteria that have been determined and do analysis using aplication SmartPLS. Based on result, sales promotion have no significant effect on impulsif buying with value of significant is 1,994. From another result of product quality and electronic word of mouth have significant effect on impulsif buying with value of significant is 2,475 and 3,679. So, e-commerce Shopee must take advantage of product quality and electronic word of mouth to compete to another e-commerce company.